Nutrient cycles in three African cities - Lee-Smith, D.; Karanja, N.; Njenga, M.; Dongmo, T.; Prain, Gordon (2010)
When Urban Harvest began its sub-Saharan programme in 2002, scientists in the Consultative Group on International Agricultural Research (CGIAR) knew that crop-livestock interactions intensify with human population densities. However, little was known about the nature of these interactions at the higher densities in and around cities, such as Nairobi where the population density was on average almost ten times higher than in the rural areas at that time.